Analisis Pengaruh Brand Image dan Personal Selling terhadap Keputusan Pembelian pada Produk Human Diagnostic (Studi pada PT.Putra Airlangga Medika) - Wiem S.P, Enggar; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2016)
The developing of medical supplies and laboratorium’s reagent business are faster. The competition between companies is tighter. This situation give a decrease effect to sales of PT.Putra Airlangga Medika, as a distributor product of Human Diagnostic in Central Java and DIY. This studied’s purpose is to explain an effect service quality, product quality, and personal selling to buying decision. Brand Image is as an intervening variable between service quality and product quality. This studied was held in medical institution that spread on Central Java and DIY region..This study was conducted by taking samples using non probability sampling technique by purposive sampling method, the respondents are consumer who have bought product of Human Diagnostic. Used as a sample of 100 respondents to fill out a questionnaire which consist of open and closed quetions. The result shows that service quality and product quality has positive and significant impact on brand image with ther regression value of 0.509 and 0.450, and brand image has a positive and significant effect to buying decision with regression value of 0.439. Personal selling also has a positive and significant effect to buying decision with the regression value 0.500. First model shown that 79.8% brand image variable can be explained by service quality and product quality variable. While the second model shown 69.5% buying decision can be explained by brand image and personal selling. And for the rest can be explained by other variables that beyond research.